Regesten zur Geschichte der Juden in Österreich, Band 4: 1387-1404 - Brugger, Eveline (Studien Verlag, 2018)
The remarkably high number of medieval sources on the history of Austrian Jews provide insights into the economic, legal, and social standing of the Jews as well as into how the Christian environment treated them. The sources collected in this volume give evidence of the rulers' increased pressure on their Jewish subjects, particuarly by means of financial exploitation, and document the first open persecutions on today's Austrian territory after the Plague-related pogroms. Additionally, the source material allows for an analysis of the manifold Jewish-Christian interaction and the living conditions of the Jewish population.